The Role of Embodiment in the Perception of Music - Marc Leman; Pieter-Jan Maes (Empirical Musicology Review, 2015)
Since its breakthrough at the beginning of the twenty-first century, the embodied music cognition theory has inspired empirical research on the role of actionperception couplings in musical activities. The integration of novel technologies and analysis methods inspired empirical research advancing knowledge regarding the role of embodiment in music perception and musical signification processes. In this paper, we present recent and on-going research in the field of embodied music cognition, with a focus on studies conducted at IPEM, the research laboratory in systematic musicology at Ghent University, Belgium. Attention is devoted to encoding/decoding principles underlying musical expressiveness, synchronization and entrainment, and action-based effects on music perception. The discussed empirical findings demonstrate that embodiment is only one component in an interconnected network of sensory, motor, affective, and cognitive systems involved in music perception. Currently, these findings drive the embodiment theory towards a more dynamical approach in which the interaction between various internal processes and the external environment are of central importance. Additionally, this approach envisions practical outcomes in the field of music affect research, wellbeing, healing, sports, music engineering, and brain studies.